2014
DOI: 10.1186/s13014-014-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of lung cancer dose calculation accuracy with Monte Carlo simulation

Abstract: BackgroundThe accuracy of dose calculation is crucial to the quality of treatment planning and, consequently, to the dose delivered to patients undergoing radiation therapy. Current general calculation algorithms such as Pencil Beam Convolution (PBC) and Collapsed Cone Convolution (CCC) have shortcomings in regard to severe inhomogeneities, particularly in those regions where charged particle equilibrium does not hold. The aim of this study was to evaluate the accuracy of the PBC and CCC algorithms in lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…In the 3DCRT, both the PB and MC algorithms may be used if the treatment field does not include heterogeneities. Our results are consistent with the study by Yangun et al 24. The magnitude of the difference may be higher in the case of small treatment volumes and negligible in the case of large GTVs.…”
Section: Discussionsupporting
confidence: 93%
“…In the 3DCRT, both the PB and MC algorithms may be used if the treatment field does not include heterogeneities. Our results are consistent with the study by Yangun et al 24. The magnitude of the difference may be higher in the case of small treatment volumes and negligible in the case of large GTVs.…”
Section: Discussionsupporting
confidence: 93%
“…(8,9) One limitation of this study is that it did not directly compare the IMRT SBRT plans to 3D CRT SBRT plans. Zhao et al (17) compared the dose calculation accuracy for conventional fractionation plans, directly comparing 3D CRT and IMRT plans for 24 patients. The results of their study cannot directly compare with our study, because of different tumor volumes.…”
Section: Resultsmentioning
confidence: 99%
“…Overriding the ED of a target volume to a water‐equivalent ED is associated with better target coverage due to the fact that the CCC algorithm accounts for inhomogenieties by scaling dose kernels by the relative electron densities . Previous studies have shown that for the CCC algorithm, a lower lung ED is associated with a reduced medium target dose .…”
Section: Discussionmentioning
confidence: 99%